Hexadecadienyl monolayers on hydrogen-terminated Si(111) faster monolayer formation and improved surface coverage using the enyne moiety - Rijksen, Bart (Langmuir : the ACS journal of surfaces and colloids, 2012)
To further improve the coverage of organic monolayers on hydrogen-terminated silicon (H-Si) surfaces with respect to the hitherto best agents (1-alkynes), it was hypothesized that enynes (H-C≡C-HC═CH-R) would be even better reagents for dense monolayer formation. To investigate whether the increased delocalization of β-carbon radicals by the enyne functionality indeed lowers the activation barrier, the kinetics of monolayer formation by hexadec-3-en-1-yne and 1-hexadecyne on H-Si(111) were followed by studying partially incomplete monolayers. Ellipsometry and static contact angle measurements indeed showed a faster increase of layer thickness and hydrophobicity for the hexadec-3-en-1-yne-derived monolayers. This more rapid monolayer formation was supported by IRRAS and XPS measurements that for the enyne show a faster increase of the CH2 stretching bands and the amount of carbon at the surface (C/Si ratio), respectively. Monolayer formation at room temperature yielded plateau values for hexadec-3-en-1-yne and 1-hexadecyne after 8 and 16 h, respectively. Additional experiments were performed for 16 h at 80° to ensure full completion of the layers, which allows comparison of the quality of both layers. Ellipsometry thicknesses (2.0 nm) and contact angles (111-112°) indicated a high quality of both layers. XPS, in combination with DFT calculations, revealed terminal attachment of hexadec-3-en-1-yne to the H-Si surface, leading to dienyl monolayers. Moreover, analysis of the Si2p region showed no surface oxidation. Quantitative XPS measurements, obtained via rotating Si samples, showed a higher surface coverage for C16 dienyl layers than for C16 alkenyl layers (63% vs 59%). The dense packing of the layers was confirmed by IRRAS and NEXAFS results. Molecular mechanics simulations were undertaken to understand the differences in reactivity and surface coverage. Alkenyl layers show more favorable packing energies for surface coverages up to 50-55%. At higher coverages, this packing energy rises quickly, and there the dienyl packing becomes more favorable. When the binding energies are included the difference becomes more pronounced, and dense packing of dienyl layers becomes more favorable by 2-3 kcal/mol. These combined data show that enynes provide the highest-quality organic monolayers reported on H-Si up to now